(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2023)
Traditional cowpea cultivars are conserved in the Juruá Valley (Acre) by farmers who adopt a "beach" production system, in lowland areas on the banks of the Juruá River and tributaries. Cowpea inoculation is a sustainable and low-cost technique that has provided an increase in the growth and productivity of the crop, but that has not yet been tested in this production system. The objective of this work was to evaluate the development and production of cowpea inoculated with Bradyrhizobium strains in a traditional cultivation system in Southwestern Amazonia. A randomized block design with three replications and four treatments was used: seeds inoculated with strains BR 1808, BR 3262, and BR 3267, and a control without inoculation. Inoculation provided an increase in the majority of the studied variables. The productivity obtained in the treatments with BR 3262 and BR 1808 was superior to the other treatments. The strain BR 3262 showed higher levels of total chlorophyll and nitrogen. Inoculation with Bradyrhizobium proved to be a promising technology for the cultivation of cowpea beans in lowland soils of the Juruá River.